CRISPR-Cas9 Gene Therapy: Non-Viral Delivery and Stimuli-Responsive Nanoformulations - Hyunwoo Lee; Won-Yeop Rho; Yoon-Hee Kim; Hyejin Chang; Bong-Hyun Jun (Molecules)
The CRISPR-Cas9 technology, one of the groundbreaking genome editing methods for addressing genetic disorders, has emerged as a powerful, precise, and efficient tool. However, its clinical translation remains hindered by challenges in delivery efficiency and targeting specificity. This review provides a comprehensive analysis of the structural features, advantages, and potential applications of various non-viral and stimuli-responsive systems, examining recent progress to emphasize the potential to address these limitations and advance CRISPR-Cas9 therapeutics. We describe how recent reports emphasize that nonviral vectors, including lipid-based nanoparticles, extracellular vesicles, polymeric nanoparticles, gold nanoparticles, and mesoporous silica nanoparticles, can offer diverse advantages to enhance stability, cellular uptake, and biocompatibility, based on their structures and physio-chemical stability. We also summarize recent progress on stimuli-responsive nanoformulations, a type of non-viral vector, to introduce precision and control in CRISPR-Cas9 delivery. Stimuli-responsive nanoformulations are designed to respond to pH, redox states, and external triggers, facilitate controlled and targeted delivery, and minimize off-target effects. The insights in our review suggest future challenges for clinical applications of gene therapy technologies and highlight the potential of delivery systems to enhance CRISPR-Cas9’s clinical efficacy, positioning them as pivotal tools for future gene-editing therapies.